2010
DOI: 10.1016/s0924-9338(10)71647-3
|View full text |Cite
|
Sign up to set email alerts
|

PW01-240 - Rate Of Alcohol And Substance Use Disorders Among The Journalists In Erbil City

Abstract: Objectives: A number of studies have shown variations in the rate of alcohol and substance use disorders among different occupations, but no study till now stressed on such a variation in Iraq. The present study aimed to study variations in the rate of alcohol and substance use disorders between journalists and some other occupations in Erbil city. Methods: 200 journalists and 486 of other professionals were interviewed between the period of September to November 2008 by a structured interview (M.I.N.I.) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Descriptions of the studies are reported in Table 2. Of the included studies, only four were alcohol specific [17][18][19][20]; two were about substance use [21,22] and two about health risk behaviours [23,24]; one each was primarily focused on mental health disorders [25], smoking [26], novel psychoactive drugs [27], risky driving [28], and sleep disorders [29]. No literature was found that related to preventative strategies in relation to alcohol.…”
Section: Research Topicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Descriptions of the studies are reported in Table 2. Of the included studies, only four were alcohol specific [17][18][19][20]; two were about substance use [21,22] and two about health risk behaviours [23,24]; one each was primarily focused on mental health disorders [25], smoking [26], novel psychoactive drugs [27], risky driving [28], and sleep disorders [29]. No literature was found that related to preventative strategies in relation to alcohol.…”
Section: Research Topicsmentioning
confidence: 99%
“…Only one study recruited a sample from more than one province [25]. Four studies recruited from Baghdad [19][20][21]27] and Erbil [17,22,23,28]. Two recruited students from Karbala [18,26].…”
Section: Study Settings and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations